Potential Corruption in the Democratic Party of Village Head Election (Law Research Review Quarterly, 2018)
The Election of Village Heads (Pilkades) as a form of implementation of democracy in Indonesia at a smaller level, within the village, often causes many problems. One of the problems that arises with regard to money politics in organizing Pilkades. In fact, the principles of holding general elections, in this case the Pilkades, must also be in accordance with the applicable laws and regulations. The absence of control and law enforcement that are clearly related to fraud in the implementation of the Pilkades makes democracy not as expected. This paper examines the various potential acts of corruption that occur in the election of village heads.